Body Composition in Swiss Elite Wheelchair Athletes - Flueck, Joelle Leonie (Frontiers in Nutrition, 2020)
The aim of this study was to retrospectively interpret body composition in various wheelchair athletes. In total, 69 athletes (mean ± standard deviation; age 33 ± 11y; body mass 65.1 ± 14.8kg; height 169.9 ± 14.9cm and time since injury 19 ± 11y) from different national teams in wheelchair sports underwent a dual x-ray absorptiometry (DXA) measurement during the yearly medical check-up. The data showed a significant difference between total fat and total fat-free mass between male (fat mass: 15.1 ± 7.6kg; fat-free mass: 51.8 ± 9.3kg) and female (fat mass: 19.4 ± 7.8kg; fat-free mass: 36.8 ± 7.6kg) athletes (p=0.032, p<0.001). In contrast, no significant difference (p=0.16, p=0.07) in fat and fat-free mass between paraplegic, tetraplegic and non-SCI athletes was found. Comparing different sports, the lowest fat mass was found in paracycling athletes whereas curling game players showed the highest total fat mass. Basketball game players showed the highest fat-free mass (fat-free mass: 54.8 ± 10.1kg). In tetraplegic athletes, difference in fat-free mass between left and right arms correlated with the upper extremity motor score. For the interpretation of the data it seems to be crucial, that many different parameters (ie. gender, motor level of the injury) are taken into consideration in wheelchair athletes.